Assessing changes in stethoscope hygiene during COVID-19: a multi-centre cross-sectional study. (September 2022) - Vasudevan, R.S.; Nedjat-Haiem, M.A.; Mahadevan, A.; Herbert, M.S.; Lander, L.; Warsi, T.; Shaikh, U.; Harding, C.; Savoia, M.C.
Summary: Background: The COVID-19 (SARS-CoV-2) pandemic has increased infection control vigilance across several modes of patient contact. However, it is unknown whether hygiene pertaining to stethoscopes, which carry the potential for pathogenic contamination, has also shifted accordingly. Aim: To characterize pandemic-related changes in stethoscope hygiene. Methods: We surveyed healthcare providers at three major medical centres. Questions quantitatively (Likert scale and frequency) assessed stethoscope hygiene beliefs and practices with two components: before and during COVID-19. Participants were grouped based on performance of optimal stethoscope hygiene (after every patient) before and during COVID-19. Groups were compared using χ 2 and analysis of variance (ANOVA). Findings: Of the 515 (10%) who completed the survey, 55 were excluded ( N = 460). Optimal hygiene increased from 27.4% to 55.0% ( P < 0.001). There were significant increases in Likert scores for all questions pertaining to knowledge of stethoscope contamination ( P < 0.001). Belief in stethoscope contamination increased ( P < 0.001) despite no change in perceived hygiene education. Resident physicians were less likely compared with attending physicians and nurses to have adopted optimal hygiene during COVID-19 ( P < 0.001). Conclusion: Despite a positive shift in stethoscope hygiene during COVID-19, optimal hygiene was still only performed by around half of providers. Educational interventions, particularly targeting early-career providers, are encouraged.